Genome-wide identification, expression analysis, and potential roles under low-temperature stress of bHLH gene family in Prunus sibirica - Liu, Quangang; Wen, Jiaxing; Wang, Shipeng; Chen, Jianhua; Sun, Yongqiang; Liu, Qingbai; Li, Xi; Dong, Shengjun (Frontiers in Plant Science, 2023)
The basic helix-loop-helix (bHLH) family is one of the most well-known transcription factor families in plants, and it regulates growth, development, and abiotic stress responses. However, systematic analyses of the bHLH gene family in Prunus sibirica have not been reported to date. In this study, 104 PsbHLHs were identified and classified into 23 subfamilies that were unevenly distributed on eight chromosomes. Nineteen pairs of segmental replication genes and ten pairs of tandem replication genes were identified, and all duplicated gene pairs were under purifying selection. PsbHLHs of the same subfamily usually share similar motif compositions and exon-intron structures. PsbHLHs contain multiple stress-responsive elements. PsbHLHs exhibit functional diversity by interacting and coordinating with other members. Twenty PsbHLHs showed varying degrees of expression. Eleven genes up-regulated and nine genes down-regulated in -4℃. The majority of PsbHLHs were highly expressed in the roots and pistils. Transient transfection experiments demonstrated that transgenic plants with overexpressed PsbHLH42 have better cold tolerance. In conclusion, the results of this study have significant implications for future research on the involvement of bHLH genes in the development and stress responses of Prunus sibirica.